A Dangerous Journey : Inside Another Year in Boxing - Hauser, Thomas (Book collections on Project MUSE., 2019)
"A Dangerous Journey is a collection of Thomas Hauser's writing on boxing over the course of the 2018 season. He turns his award-winning investigative reporting skills on the scandal surrounding the use of illegal performance enhancing drugs in boxing today and the failures of corrupt and incompetent state athletic commissions. Hauser also takes readers into Canelo Alvarez's dressing room in the hours before and after his rematch against Gennady Golovkin, the biggest fight of the year, and offers in-depth portraits of boxing's biggest stars--past and present--as well as reflections on fight-related curiosities ranging from Ronda Rousey to David and Goliath"--